2019
DOI: 10.1111/bjd.17529
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions to support the early detection of skin cancer through skin self‐examination: a systematic review and meta‐analysis

Abstract: Summary Background As skin cancer incidence rises, there is a need to evaluate early detection interventions by the public using skin self‐examination (SSE); however, the literature focuses on primary prevention. No systematic reviews have evaluated the effectiveness of such SSE interventions. Objectives To systematically examine, map, appraise and synthesize, qualitatively and quantitatively, studies evaluating the early detection of skin cancer, using SSE interventions. Methods This is a systematic review (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Dear Editor, Ersser and colleagues’ review of interventions to promote skin self‐examination is timely and relevant, insofar as the topic is of considerable current clinical and research interest. However, it is subject to two significant limitations.…”
mentioning
confidence: 99%
“…Dear Editor, Ersser and colleagues’ review of interventions to promote skin self‐examination is timely and relevant, insofar as the topic is of considerable current clinical and research interest. However, it is subject to two significant limitations.…”
mentioning
confidence: 99%
“…In this issue of the BJD , Ersser et al . systematically review behavioural interventions that promote skin self‐examination, highlighting future research frontiers.…”
mentioning
confidence: 99%
“…Digital technology could also be used to create social support for skin checking, by linking people with a checking partner who could remind and encourage each other to conduct the desired behaviour. As Ersser and colleagues rightly argue, future interventions should creatively integrate apps and digital devices into their intervention and outcome measurement tools to increase the validity of benefit assessment. In contrast, future studies solely relying on self‐reported outcomes should be discouraged as they are unlikely to move the field forward.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…D ear E ditor , Further to Coups’ letter on our systematic review and meta‐analysis of interventions promoting skin self‐examination (SSE), of the ‘reviews’ cited, one is a systematic review and the other a scoping review . The interventional focus of Wu et al .…”
mentioning
confidence: 99%